Vibronic coupling density analysis and quantum dynamics simulation for singlet fission in pentacene and its halogenated derivatives - Nagami, Takanori; Tonami, Takayoshi; Okada, Kenji; Yoshida, Wataru; Miyamoto, Hajime; Nakano, Masayoshi (The Journal of chemical physics, 2020)
We theoretically investigate microscopic origins of vibronic coupling (VC) contributing to singlet fission (SF) dynamics in pentacene and its halogenated derivatives. The features of VCs related to diabatic exciton states and interstate electronic couplings (Holstein and Peierls couplings, respectively) are interpreted by the VC density (VCD) analysis, which allows one to clarify the relationship between the chemical structure and VC as spatial contribution. It is found for the pentacene dimer face-to-edge configuration in a herringbone crystal that characteristic intermolecular vibrations with low frequencies exhibit strong Holstein couplings for the intermediate charge-transfer (CT) exciton states as well as Peierls couplings. From VCD analysis, the comprising density of the intermolecular CT and that of the intermolecular vibration are found to be constructively mixed in the intermolecular space, leading to the enhancement of VC. Moreover, in order to assess the chemical modification manner for controlling VC, we design several halogenated pentacene derivatives with slip-stack configurations. Our strategy to enhance VCD by halogenation is found to be rational, whereas the peaks of VC spectra for the CT states in the slip-stack packings are observed in high frequency regions. We compare their SF dynamics based on the quantum master equation explicitly including the exciton state-dependent VCs. From the analysis on relative relaxation factors between the adiabatic exciton states, their difference in the SF rate is highlighted by exciton configurations in addition to VCs. The present study is expected to be a first step toward efficient SF based on the design of VC in terms of both the chemical structure and intermolecular packing.